Gynecological disorders of adolescent girls at Kathmandu Medical College Teaching Hospital - Karki, Chanda; Shrestha, Nira Singh; Rayamajhi, Roshan T (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aim: To assess the gynecological disorders in adolescents and to study the menstrual disorders in the study group. Result: A total of 1697 adolescent girls aged 13 to 19 years attending the gynecological outpatient department of KMCTH were included in the study. Their detail history was taken followed by general and systemic examinations and investigations like hemogram, coagulation profile, hormonal assays, and ultrasonography as per need were performed. Thus their gynecological problems including menstrual disorders were identified. With this information the details of their menstrual abnormalities were also analyse. Teenage pregnancy was the most frequently observed (56.33%) diagnosis. Menstrual disorders were found to be the second most common (23.80%) gynecological problem. They varied from amenorrhea (29.20%) to menorrhagia. Dysfunctional uterine bleeding was the commonest etiology of menstrual dysfunction (204/286) in the study group. Conclusion: Unsafe abortion and sexually transmitted infections were some of the other problems of adolescent girls. It is important to note that adolescents are not a homogenous group. Their needs vary with their sex, stage of development, life circumstances and the socioeconomic conditions of their environment. This is the time when they have the maximum burden of education and career building on their shoulders. They are the group who hesitate to seek services from traditional facilities. Therefore every health institution should initiate or strengthen adolescent friendly services and provide specialist care to this special group of people. DOI: http://dx.doi.org/10.3126/njog.v3i2.10831 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 44-47